Los problemas sociales y económicos y su grado de influencia en el desarrollo comunitario de la comuna Gradas, parroquia San Simón, cantón Guaranda - Chela Chela, Willian Víctor (2016)
The systematization of the major social and economic problems existing in the Gradas commune, San Simon county, Canton Guaranda highlights Community Development, by describing facts and actual data in local development plans and the Development Plan of Self-Government San Simon parish; also it contains information gathered by applying the interview with the direct participation of community actors, who demonstrated a vision to achieve the good life "Sumak Kawsay" to assume the development and responsibility of human groups, focused on the human capital development through the conservation of natural capital with transverse axes: multiculturalism, identity, environment and food sovereignty. Has been very important to describe the real situation, objective and updated harrows commune, especially in the social and economic aspects as a starting point to establish the degree of influence of these aspects against the Community Development territory referred to above, for which I had to analyze the following major components: forms of social organization, cultural elements, system of indigenous law and authority, the management of natural resources is also added, spirituality and production, concurrent with technological progress, globalization of phenomena social of the province and the Ecuadorian state. The study of this work is prioritized on a systematization of experience Community Development environment, which allows us to know the organization process, reconstruction based on testimonies of experience and direct communication of the board and its members. As a result of the conducted systematic findings related to the main most important historical landmarks in the community is generated, the particularities of the community process undertaken by them, their forms of participation and organization at different times, which allow us to interpret them to conclude on lessons learned.